1986
DOI: 10.1007/bf01645204
|View full text |Cite
|
Sign up to set email alerts
|

Zur Gewebekonzentration und Wirksamkeit von Ofloxacin bei chirurgischen Patienten

Abstract: Following a 400 mg preoperative oral dose, ofloxacin concentrations were measured preoperatively in serum and at the time of tissue removal in serum, gall bladder fluid, the gall bladder wall, liver tissue, muscle, fascia, subcutaneous fat and skin. Serum values were more or less constantly above 3 mg/l at all times. The highest intraoperative ofloxacin concentration was 11.85 mg/l in the gall bladder fluid. In the gall bladder wall, liver and muscle, concentrations were slightly higher than in the serum, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Therapeutic levels were also found in blister fluid (31,61), infected bone (18, 61), soft tissue (32), skin (11,32), muscle (11,18,61), liver (11), gynecological tissues (23,60), prostate (6,61), and pleural fluid (61). IN …”
Section: Vitro Activitymentioning
confidence: 99%
“…Therapeutic levels were also found in blister fluid (31,61), infected bone (18, 61), soft tissue (32), skin (11,32), muscle (11,18,61), liver (11), gynecological tissues (23,60), prostate (6,61), and pleural fluid (61). IN …”
Section: Vitro Activitymentioning
confidence: 99%
“…In patients with T tube biliary drainage, the ofloxacin concentration in T tube bile, 2 h after a single 200-mg dose, was 7.28 B 3.45 Ìg/ml. Duben et al [135] reported an ofloxacin concentration of 3.31 B 2.05 Ìg/ml in serum, 11.85 B 4.75 Ìg/ml in gallbladder bile, 4.59 B 2.72 Ìg/ml in gallbladder wall and 4.59 B 3.46 Ìg/ml in liver during cholecystectomy scheduled 9-10 h after a 400-mg single dose.…”
Section: Ofloxacinmentioning
confidence: 99%